2013
DOI: 10.1002/14651858.cd002796.pub2
|View full text |Cite
|
Sign up to set email alerts
|

'Scared Straight' and other juvenile awareness programs for preventing juvenile delinquency

Abstract: Background 'Scared Straight' and other similar programs involve organized visits to prison by juvenile delinquents or children at risk for criminal behavior. Programs are designed to deter participants from future offending through firsthand observation of prison life and interaction with adult inmates. These programs remain in use despite research questioning their effectiveness. This is an update of a 2002 review. Objectives To assess the effects of programs comprising organized visits to prisons by juvenile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 17 publications
2
56
1
1
Order By: Relevance
“…When harms have been studied in psychosocial trials, they have mainly involved youth-focused interventions and have been defined as main effects in the unintended direction. 97,98 Recent systematic reviews of parenting interventions have not found evidence of harmful effects defined in this way. 12 Parents rarely report potentially harmful outcomes in qualitative studies; Morch et al 51 mention none, despite interviewing many parents for whom intervention was not successful.…”
Section: Potential Harmful Effects Of Parenting Interventionsmentioning
confidence: 99%
“…When harms have been studied in psychosocial trials, they have mainly involved youth-focused interventions and have been defined as main effects in the unintended direction. 97,98 Recent systematic reviews of parenting interventions have not found evidence of harmful effects defined in this way. 12 Parents rarely report potentially harmful outcomes in qualitative studies; Morch et al 51 mention none, despite interviewing many parents for whom intervention was not successful.…”
Section: Potential Harmful Effects Of Parenting Interventionsmentioning
confidence: 99%
“…This lack of critical appraisal has been seen in vitally important areas such as the mitigation of posttraumatic stress disorder, the reduction of family violence, the elimination of racial prejudice, the reduction of sex differences in mathematics, and the lessening of adolescent behavior problems and drug use (64)(65)(66)(67)(68)(69)(70)(71). In one example, a therapy called "Critical Incident Stress Debriefing" was broadly implemented throughout the United States to reduce posttraumatic stress disorder, even though this costly program simply did not work and, in fact, sometimes worsened the very stress it was meant to resolve (67).…”
Section: Extended Implicationsmentioning
confidence: 99%
“…It is sobering to contrast the CMO theory-focused and theory-testing evaluation of the Comet crashes with the theory-specification and testing indifference of the meta-analysis of Scared Straight (Petrosino et al, 2002), which found that criminality seemed to be produced rather than reduced. The systematic review included a) no analysis of points where the scared straight theory might be wanting; b) no proposals for or tests of alternative theory that might explain the negative effects; and c) no findings identifying the sub-groups where mechanisms were activated to produce negative effects.…”
Section: Emmie and Engineeringmentioning
confidence: 99%